The evolution of three generations of platelet concentrates products: a leap from classical formulations to the era of extracellular vesicles - Li, Youan; You, Huimin; Ou, Chunhui; Zhu, Hongyuan; Cheng, Biao; Tian, Ju (Frontiers in Bioengineering and Biotechnology, 2025)
Platelet concentrates (PCs) have evolved from classical formulations to exosome-based therapies, reflecting a paradigm shift in regenerative medicine. This review analyzes three generations of PCs products, comparing their technological progress, functional differences, and clinical applications. It proposes a novel function-driven classification system that redefines PCs generations based on biological activity rather than chronological development. First-generation PCs, such as platelet-rich plasma (PRP) and platelet-rich growth factor plasma (PRGF), employ centrifugation to concentrate platelets but exhibit limited therapeutic duration due to rapid growth factor depletion and absent fibrin matrices. Second-generation PCs, including platelet-rich fibrin (PRF) and concentrated growth factor (CGF), form natural fibrin networks through low-speed centrifugation, facilitating prolonged cytokine release, though their effectiveness depends heavily on cellular viability. Third-generation PCs represent a paradigm shift by harnessing extracellular vesicles, notably platelet-derived exosomes (PLEXOs). These 30–150 nm vesicles carry growth factors, miRNAs, and lipids, mediating targeted intercellular signaling, immune regulation, and regenerative processes. PLEXOs exhibit greater therapeutic efficacy than previous PCs generations in diverse clinical contexts. Our systematic analysis of PCs evolution and underlying molecular mechanisms addresses three key limitations of extracellular vesicle-based therapies: poor isolation efficiency, regulatory ambiguity, and inconsistent treatment protocols. Critical challenges persist in standardizing extracellular vesicle isolation, scaling production, and validating long-term safety. Future solutions may involve engineered extracellular vesicles, genomic editing, and aptamer-functionalized precision theranostics. The proposed “PRP rapid activation → PRF scaffolding → PLEXOs repair” tri-step therapy demonstrates how intergenerational synergies could advance regenerative medicine with enhanced precision and clinical potential.